Analisa Qashidah Nahdliyyah Karya M. Faisol Fatawi: Kajian Resepsi Sastra Prespektif Hans Robert Jauss - Jambak, Mellinda Raswari; Rarasati, Indah -; Hakim, Arif Rahman (Afshaha: Jurnal Bahasa dan Sastra Arab, 2022)
Every human being has his own view in assessing a literary work. These views can be collected and used as an assessment of a literature. The existence of different receptions in responding to a literary work raises a unique thing. By studying literature through Hans Robert Jauss's theory of literary reception, it can be a material for introspection for authors and readers as well as assessing the superiority or value of the literary work. This study aims to (1) describe how UIN Malang students respond to Qasidah Nahdliyyah, (2) describe the horizon of readers' expectations of Qashidah Nahdliyyah, (3) describe the factors that cause differences in responses and horizons of readers' expectations. The theory used is Hans Robert Jauss' literary reception called Horizon Harapan. This research is presented in the form of a table containing the results of the researcher's questionnaire to several students. The results of this study are the discovery of factors that cause variations in responses and horizons of readers' expectations in the form of: (1) the reader's experience in studying literary works, (2) the reader's knowledge of poetry and its building elements, (3) self-identity, education, and The respondent's family background is not a factor in the differences in literary receptions.